Pengaruh Penggunaan TikTok terhadap Perubahan Gaya Bahasa Komunikasi Interpersonal di Kalangan Mahasiswa - Elviani Intan Saputri; David Rizar Nugroho; Enden Darjatul Ulya; Mulyono Mulyono (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2025)
This study investigates the influence of TikTok usage on the changes in interpersonal communication styles among university students in Indonesia. The rapid development of digital communication platforms, especially TikTok, has reshaped the way young people interact, express themselves, identify changes in their interpersonal communication styles, and analyze the effect of TikTok usage on those changes. Using a quantitative survey method with 100 active university students as respondents, data were collected through an online questionnaire. The results indicate that students’ TikTok usage is categorized as high, particularly in terms of frequency, duration, and engagement intensity. Findings also show a significant shift in communication styles, especially in language choice, expressive patterns, and interaction modes. Simple linear regression analysis confirms that TikTok usage has a strong and significant influence on changes in interpersonal communication styles (p < 0,001; R² = 0,944). These results demonstrate that TikTok not only serves as an entertainment platform but also plays a substantial role in shaping students’ communication behavior. The study highlights important implications for understanding digital communication trends among young adults in Indonesia.